Spectroscopic properties of Yb3+/Er3+ - doped antimony-phosphate glasses for fiber amplifiers - Zmojda, Jacek; Dorosz, Dominik; Kochanowicz, Marcin; Dorosz, Jan (Photonics Letters of Poland, 2010)
In this paper the optical spectroscopic properties of Yb3+/Er3+ co-doped antimony-phosphate glasses were investigated. The absorption and luminescence spectra were measured and the emission cross-section for 4I13/2 -> 4I15/2 transition of Er3+ was calculated on the basis of McCumber theory. The resonant energy transfer (ET) between Yb3+ -> Er3+ ions was investigated pumping at 976nm. As a result of optimization of rare earth concentration the best efficiency of energy transfer in fabricated glasses was obtained for molar composition 1%Y2O3 : 0.5%Er2O3. Full Text: PDF References M. Liao, Z. Duan, L.Hu, Y. Fang, L.Wen,"Spectroscopic properties of Er3+/Yb3+ codoped fluorophosphate glasses", J. Lum 126 139 (2007)[CrossRef] L. Zang, H. Hu, C. Qi, F. Lin,"Spectroscopic properties and energy transfer in Yb3+/Er3+-doped phosphate glasses", Opt. Mat. 17 371 (2001)[CrossRef] J. F. Philipps, T. Töpfer, H. Ebendorff - Heidepriem, D. Ehrt, R.Sauerbrey,"Appl. Phys. B72 399 (2001)", Spectroscopic and lasing properties of Er3+:Yb3+-doped fuoride phosphate glasses[CrossRef] Y. Fang L. Hu, M. Liao L. Wen J. Alloys Comp. 457 19 (2008) Qian, C. Zhao, G.F. Yang, Z.M. Yang, Q.Y. Zhang, Z.H. Jiang"Spectroscopic properties of Er3+-doped Na2O?Sb2O3?B2O3?SiO2 glasses", J. Non-Cryst. Solids 354 1981 (2008)[CrossRef] W.J. Miniscalco, R.S. Quimby,"General procedure for the analysis of Er3+ cross sections", Opt. Lett. 16 (1991)[CrossRef] Q. Qian, Q.Y. Zhang, H.F. Jiang Z.M. Yang, Z.H. Jiang,"The spectroscopic properties of Er3+-doped antimony?borate glasses", Physica B 405 2220 (2010)[CrossRef]